If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 3u = -6 Solving -3 + 3u = -6 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3u = -6 + 3 Combine like terms: -3 + 3 = 0 0 + 3u = -6 + 3 3u = -6 + 3 Combine like terms: -6 + 3 = -3 3u = -3 Divide each side by '3'. u = -1 Simplifying u = -1
| 2b=-5-3b | | 16=5-0.125 | | 2(5x-4)-3(4x+3)=-43 | | 187/16=X | | -17-2x=6-6 | | -7(8+4x)=-140 | | 10a-6b-5a-10b= | | 13x+-17x=180 | | 2(3m+3)=3(2m+4) | | 5(-8+x)=-30 | | 40x+3.6+x=1.2 | | x+7*3-2/5=11 | | 8(1-z)=4(1+2x)+6 | | 61-5+2(1-2)= | | -24.2-m=25.2 | | 4+2=6x+2x | | -3(2m-1)=-6m+3 | | x^2(x+4)(x-4)=0 | | 3(4x+6)=-78 | | 2x^2-28x/4x^2-16x | | 12x-(2/3)=1 | | 39.21+2.65=42.03x | | -11u=22 | | 1-6x+5=12 | | 4.50m+.15c=9 | | x(9x+9)=4x^2-2x+36 | | 222/12 | | 8x-20=15+x | | 3x+5=x+4x+5-2x | | (x-4)=8-16 | | -11=17x | | 1234+5432=6666 |